Análisis topológico de la red de transporte público en el área urbana de León (Estudios humanísticos. Geografía, historia y arte, 1989)
The analysis of the public transport network in the urban arca of.Leon allows us to show two interesting questions: (a) the difference between private and semipublic service has a direct influence in the graph structure. (b) The service to the urban centre is the main reason of the urban transport, determining in this way the distribution of the accesibility